Optimisation of Ultra-High-Performance Concrete with Special Quarry Dust - Alizada, Amir Mohammad; Waseem, Ehsanullah; Abdul Kudus, Sakhiah; Mohd Jaini, Zainorizuan (International Journal of Integrated Engineering, 2023)
The cement composition of concrete directly affects the CO2 emissions to the environment. UHPC (Ultra High-Performance Concrete) is a new type of concrete rapidly gaining popularity in the building industry due to its superior strength and endurance. In contrast to regular concrete, UHPC requires more than twice as much cement, making it more expensive and leaving a more significant carbon imprint. In this study, waste cement was substituted with 4%, 8%, and 12% special quarry dust from a manufacturer in Kuantan, Malaysia. Maximum compressive strength and quarry dust percentage are determined through experimentation and assessed in Design Expert Software. This investigation tested modified UHPC for strength, durability, and scanning electron microscope (SEM) appearance. Experiments show that substituting 21% quarry dust for cement yields the best outcomes. Since the particle size of quarry dust is finer than that of other matrices, it helps to reduce voids and boosts the UHPC’s endurances. The quarry dust adds filler and a minor increase in viscosity to the UHPC, which is a better replacement for anhydrate cement in filler applications.